Periodic solutions of a delayed predator-prey model with stage structure for predator - Rui Xu; M. A. J. Chaplain; F. A. Davidson (Journal of Applied Mathematics)
A periodic time-dependent Lotka-Volterra-type predator-prey model with stage structure for the predator and time delays due to negative feedback and gestation is investigated. Sufficient conditions are derived, respectively, for the existence and global stability of positive periodic solutions to the proposed model.